Ancient Households of the Americas Conceptualizing What Households Do - Douglass, John G; Gonlin, Nancy (University Press of Colorado, 2012)
Several different cultures - Iroquois, Coosa, Anasazi, Hohokam, San Agustín, Wankarani, Formative Gulf Coast Mexico, and Formative, Classic, Colonial, and contemporary Maya - are analyzed through the lens of household archaeology in concrete, data-driven case studies."This excellent book should be heavily used by anyone with an interest in household archaeology."-North American Archaeologist"There are a number of excellent studies that scholars interested in household archaeology will find highly useful." -Journal of Anthropological Research"This collection underscores the importance of household archaeology to the study of social dynamics." -Choice"This volume is an impressive one. . . . In an era in which household archaeology has become essential to archaeological praxis, this volume is indeed essential reading."-Cambridge Archaeological Journal